Pengaruh Faktor Psikologis dalam Pemilihan Program Keahlian Teknik Mesin di Sekolah Menengah Kejuruan - Dwi Rahdiyanta (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
The purpose of the study was to determine the effect of psychological factors of students, composed of self-understanding, information literacy, and attitudes, to the choice of entering mechanical engineering study program in Vocational High Schools (VHSs) by Junior High School graduates. The research is a correlational ex post facto study. The population was 1095 students and the sample was 300 students which was sampled using proportional random sampling technique using the Krejcie and Morgan formula. The data were collected through inventories, observation sheets, and documents. The content validity was assessed through expert judgment. The construct validity was assessed using the factor analysis and the reliability using the Cronbach's Alpha formula. The data were analysed using descriptive analysis, regression analysis, and path analysis at a significance level of 0.05. The results show that: (1) There are positive and significant effects of information literacy, self-understanding and attitudes to the choice of mechanical engineering study program in VHSs; (2) Psychological factors, such as information literacy, self-understanding and attitudes, have significant effects, either directly or indirectly, to the choice of mechanical engineering study program in VHSs by Junior High Schools graduates. Tujuan penelitian ini adalah untuk mengetahui pengaruh faktor psikologis siswa yang terdiri dari aspek pemahaman diri, penguasaan informasi, dan sikap terhadap pemilihan program keahlian teknik mesin di SMK oleh para lulusan siswa SMP/MTs. Penelitian yang dilakukan merupakan penelitian korelasional dan bersifat ex-post facto. Populasi penelitian berjumlah 1095 orang siswa. Jumlah sampel penelitian sebanyak 300 siswa ditentukan dengan formula Krejcie dan Morgan. Pengambilan sampel dilakukan dengan teknik proportional random sampling. Data dikumpulkan dengan inventori, lembar pengamatan dan dokumentasi. Hasil penelitian menunjukkan bahwa: (1) Ada pengaruh yang positif dan signifikan penguasaan informasi, pemahaman diri, dan sikap siswa terhadap pemilihan program keahlian teknik mesin di SMK; (2) Faktor psikologis berupa penguasaan informasi, pemahaman diri dan sikap siswa memiliki pengaruh yang signifikan baik secara langsung maupun tidak langsung dalam menentukan pemilihan program keahlian teknik mesin di SMK bagi siswa lulusan SMP/MTs